SIKAP DAN PERILAKU ANGGOTA DPRD KOTA PEKANBARU DALAM FUNGSI LEGISLASI TAHUN 2015 ( STUDI TENTANG RANCANGAN PERATURAN DAERAH PEMBERDAYAAN MASYARAKAT BERBASIS RUKUN WARGA) - Claudia Asficha; Irwan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Moral behaviour and Attitudes of Council of Pekanbaru City members are interesting to investigate because ethical and moral issues also begin to be considered since the drafting of local regulations to the implementation of local regulations and enforcement in the midst of society. The ethical and moral factors underlying this stage are very important and very strategic in the development of this nation and state and greatly determine the shape and form and the resulting regulatory character and conditions of society that will be created by the regulationThe purpose of this research is to know attitude and behavior of DPRD member of Pekanbaru City in function of legislation year 2015 in discussion of Ranperda PMB-RW. The type of research used is descriptive qualitative research method. The location of this research is conducted in Pekanbaru City DPRD Office. Data collection techniques were conducted with interviews and documentation.The results of this research can be seen that the attitude is not mutually open among fellow members of the board because members of the Pansus who came from the PDIP faction claimed to have not received a draft of the Ranperda and decided to Walk Out because from the beginning did not agree to the ratification of this regulation.Keywords: PMB-RW, Moral Behaviour, Attitude, Counsil Of Pekanbaru City, Legislation